2019
DOI: 10.1016/j.scr.2019.101480
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of human induced pluripotent stem cells (iPSC) CSSi007-A (4383) from Joubert Syndrome

Abstract: Joubert syndrome (JS) is an autosomal recessive neurodevelopmental disorder, characterized by congenital cerebellar and brainstem defects, belonging to the group of disorders known as ciliopathies, which are caused by mutations in genes encoding proteins of the primary cilium and basal body. Human induced pluripotent stem cells (hiPSCs) from a patient carrying a homozygous missense mutation (c.2168G > A) in AHI1, the first gene to be associated with JS, were produced using a virus-free protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In this light, iPSCs represent a simple and efficient model to study abnormal neuronal development in ciliopathies such as JS. To date, a few studies have reported the generation of iPSCs carrying mutations in JS-related genes, including AHI1 (Rosati et al 2018 ; Altieri et al 2019 ; Serpieri et al 2023 ), CPLANE1 (Ali et al 2020 ), CC2D2A (Ali et al 2021 ), CEP290 (Shimada et al 2017 ; May-Simera et al 2018 ), RPGRIP1L (Wang et al 2019 ), and TMEM67 (Barabino et al 2020 ); however, these studies did not systematically analyze differentiation markers or compare ciliary phenotypes. The present study employed iPSCs derived from patients carrying pathogenic variants in four of the five common genes causative of JS, which were differentiated towards mid-hindbrain precursors and cerebellar neurons in order to address two main research questions: (1) do JS-derived iPSCs show aberrant differentiation along the cerebellar lineage?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this light, iPSCs represent a simple and efficient model to study abnormal neuronal development in ciliopathies such as JS. To date, a few studies have reported the generation of iPSCs carrying mutations in JS-related genes, including AHI1 (Rosati et al 2018 ; Altieri et al 2019 ; Serpieri et al 2023 ), CPLANE1 (Ali et al 2020 ), CC2D2A (Ali et al 2021 ), CEP290 (Shimada et al 2017 ; May-Simera et al 2018 ), RPGRIP1L (Wang et al 2019 ), and TMEM67 (Barabino et al 2020 ); however, these studies did not systematically analyze differentiation markers or compare ciliary phenotypes. The present study employed iPSCs derived from patients carrying pathogenic variants in four of the five common genes causative of JS, which were differentiated towards mid-hindbrain precursors and cerebellar neurons in order to address two main research questions: (1) do JS-derived iPSCs show aberrant differentiation along the cerebellar lineage?…”
Section: Discussionmentioning
confidence: 99%
“…Barabino et al also reported abnormal ciliary phenotype in a TMEM67 -mutant iPSC line, although in this case more numerous, but shorter and thinner cilia were observed, suggesting that different mutations in the same JS gene can lead to different outcomes. Moreover, iPSCs from RPGRIP1L -mutated JS patients showed a reduction in the number of ciliated neurons formed upon differentiation (Altieri et al 2019 ), while JS iPSCs mutated in CEP290 , when differentiated towards retinal epithelium lineages, showed smaller cilia associated with incomplete lineage maturation (Rosati et al 2018 ). Further in vitro observations made in other ciliopathy models, such as another iPSC line from a CEP290 -mutated patient with Leber’s congenital amaurosis and differentiated towards retinal pigment epithelium, also showed alterations in primary cilium formation and incidence (Parfitt et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Skin fibroblasts have typically been used as a cell source to produce iPSCs, while efforts have been made to derive iPSCs from more easily accessible cell types, such as human keratinocytes obtained from a hair pluck,61 peripheral blood cells62 and URECs 63. Reprogramming procedures with the Yamanaka’s factors1 2 have moved from the use of an integrating viral-based route (eg, lentiviruses or adeno-associated viruses (AAVs)), to non-integrating viral vectors or virus-free reprogramming kits, taking advantage of non-integrative episomal vectors, as those used to generate iPSCs from patients with JS 64 65…”
Section: Modelling Primary Ciliopathies: From Animal Models To Patien...mentioning
confidence: 99%